2021
DOI: 10.1371/journal.pone.0253851
|View full text |Cite
|
Sign up to set email alerts
|

Persistent homology as a new method of the assessment of heart rate variability

Abstract: Heart rate variability (hrv) is a physiological phenomenon of the variation in the length of the time interval between consecutive heartbeats. In many cases it could be an indicator of the development of pathological states. The classical approach to the analysis of hrv includes time domain methods and frequency domain methods. However, attempts are still being made to define new and more effective hrv assessment tools. Persistent homology is a novel data analysis tool developed in the recent decades that is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A difficulty in this is that it may be difficult to know what a “correct” subset of a signal is in order for it to be considered a P,Q,S, or T-wave. Additionally, information about optimal 1-cycles identified as P,Q,S, and T-waves could be combined with other existing approaches such as analyzing other persistent homology statistics, wavelet decompositions, and machine learning for automated arrhythmia detection in future work [12] [13] [17] [19] [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A difficulty in this is that it may be difficult to know what a “correct” subset of a signal is in order for it to be considered a P,Q,S, or T-wave. Additionally, information about optimal 1-cycles identified as P,Q,S, and T-waves could be combined with other existing approaches such as analyzing other persistent homology statistics, wavelet decompositions, and machine learning for automated arrhythmia detection in future work [12] [13] [17] [19] [21].…”
Section: Resultsmentioning
confidence: 99%
“…Thus the analysis of ECGs is important for accurate diagnosis and proper treatment of cardiovascular diseases. Several approaches to automated ECG analysis have been performed, including machine learning [4] [5] [6] [7] [8] [9] [10] [11], wavelet transforms [12] [13] [14] [15] [16], and persistent homology [17] [18] [19] [20] [21] [22] [23]. Due to the high accuracy required of ECG-analysis software and the fact that the bulk of ECG analysis is carried out by healthcare providers, the development of algorithms that identifies P,Q,R,S, and T-waves, measures intervals of interest, and/or detects arrhythmias is an active area of research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference ( Ignacio et al, 2019 ) demonstrated how to map ECGs onto high-dimensional point clouds through delayed embedding to extract topological features and finally apply random forests for classification. Study ( Graff et al, 2021 ) examined when persistence diagram was obtained by SLS filtering, and a set of indicators was extracted to distinguish the RR interval of healthy subjects and stroke patients. In addition ( Yan et al, 2019 ) applied TDA to reconstruct a signal point cloud to extract persistent landscape features to classify heart rate variability.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamical system analysis is used to model cardiac dynamical system through phase space reconstruction [ 16 , 17 , 18 , 19 , 20 ]. Topological data analysis transforms ECG signals into point clouds by time-delay embedding or Fourier transform and then extracts topological features from point clouds [ 21 , 22 , 23 , 24 , 25 , 26 ]. Above mentioned methods are adaptive with different applied conditions.…”
Section: Introductionmentioning
confidence: 99%